"That Sure is Racist": Classroom Race Talk as Resistance. Issue 7 (September 2020) - Sosa, Teresa
This work analyzed three grade 9 English Language Arts classroom discussions and contributions by Black youth as resistance acts. Using a framework of resistance based on an indigenous understanding of progress provided insight into how student resistance emerged in language as metaphor and stories. Thematic analysis of the three classroom discussions indicate student resistance is captured in the naming of what is often left silent or often silenced. Through transgressing evasion and silence, students' counter stories and experiences shared in the classroom named social realities inscribed in their day-to-day experiences, as well as how schools are complicit in silencing the lives and history of Black and indigenous people. This work demonstrates the importance of situating resistance as counter narratives that work to reconfigure interpretations of personal and social identities situated more completely within embodied experiences.